Offshoring and sequential production chains: A general equilibrium analysis - Philipp Harms; Jaewon Jung; Oliver Lorz (Canadian Journal of Economics/Revue canadienne d'économique, 2021)
We present a two-region general equilibrium model in which firms exploit international wage differences by offshoring parts of the production process. Firms have to take into account that production steps follow a strict sequence and that transporting intermediate goods across borders is costly. We analyze how a change in transport costs affects offshoring patterns as well as factor prices, accounting for the general equilibrium effects of firms' decisions. As we demonstrate, a decline in transport costs is likely to have a non-monotonic influence on relative wages and on the volume of offshoring depending on the emergence of different firm types, with domestic wages first decreasing as lower transport costs induce firms to perform large parts of the production chain abroad and then increasing as even lower transport costs provide an incentive to select the lowest-cost location for each production step.
Keywords: 330